Entrepreneurial intention in higher education during COVID-19: Evidence of stability and comparability across student groups and time - Brás, G. R. (Education and Training, 2026)
Purpose The main objective of this paper is to assess the measurement invariance of a short questionnaire assessing students' entrepreneurial intention (EI) over time and across key subgroups (gender, higher education institution (HEI) typology, course typology) during the COVID-19 pandemic. Design/methodology/approach A multigroup confirmatory factor analysis was conducted on data collected from undergraduate students enrolled in entrepreneurship modules at Portuguese HEIs during the second semester of the 2019/2020 academic year. Findings There is evidence of configural, metric and scalar invariance of the covariance structure of the 6-item scale of students' EI by gender, HEI typology and course typology, and over time (before and after entrepreneurship modules). In the context of the COVID-19 pandemic, these findings suggest that the 6-item scale of EI is psychometrically equivalent across key subgroups of entrepreneurship students in HEIs and over time. Practical implications Although it is difficult to foster students' EI in a pandemic context, those responsible for higher education must be ready to introduce new pedagogical tools in future emergency situations. Originality/value This study introduces a crisis-sensitive framework for entrepreneurial intention measurement that integrates contextualist, planned behaviour, and digital entrepreneurship perspectives. By theorising crisis-driven contextual convergence and platform-enabled homogenisation, it refines contextualist, planned behaviour, and digital entrepreneurship perspectives on intention stability under disruption and clarifies when EI comparisons remain psychometrically valid in turbulent environments.